Synthesis and optimization of energy integrated advanced distillation sequences - Li, Qing; Finn, Adrian J.; Doyle, Stephen J.; Smith, Robin; Kiss, Anton A. (Separation and purification technology, 2023)
•Novel effective routes for eco-efficient separation by distillation sequences.•Simultaneous optimization of all design degrees of freedom in distillation sequences.•Optimal arrangement of complex columns sequencing for NGL separation. This paper explores the basis on which reliable screening of distillation sequences for energy-efficient separation of zeotropic multicomponent mixtures can be carried out. A case study for the separation of natural gas liquids is used to demonstrate the approach. To solve this generic problem, a screening algorithm has been developed using optimization of a superstructure for sequence synthesis using shortcut models, in conjunction with a transportation algorithm for the synthesis of the heat integration arrangement. Different approaches for the inclusion of heat integration are explored and compared. The best few designs from this screening are then evaluated using rigorous simulation. It has been found that separation problems of the type explored can be screened reliably using shortcut distillation models in conjunction with the synthesis of heat exchanger network designs. Non-integrated designs using thermally coupled complex columns show much better performance than the corresponding designs using simple columns. However, once heat integration is included the difference between designs using complex columns and simple columns narrows significantly.